2016
DOI: 10.1063/1.4959243
|View full text |Cite
|
Sign up to set email alerts
|

Spin dynamics of an individual Cr atom in a semiconductor quantum dot under optical excitation

Abstract: We studied the spin dynamics of a Cr atom incorporated in a II-VI semiconductor quantum dot using photon correlation techniques. We used recently developed singly Cr-doped CdTe/ZnTe quantum dots (A. Lafuente-Sampietro et al., [1]) to access the spin of an individual magnetic atom. Auto-correlation of the photons emitted by the quantum dot under continuous wave optical excitation reveals fluctuations of the localized spin with a timescale in the 10 ns range. Cross-correlation gives quantitative transfer time be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Therefore, optical manipulation of a single magnetic ion spin is possible not only in classical systems with a single Mn 2+ ion in QDs with a relatively low energy gap, CdTe/ZnTe [2][3][4][5][6] and InAs/GaAs [7][8][9], but also in QDs with a higher-energy gap such as CdSe/ZnSe [1,[10][11][12] or in QD systems doped with impurities considered previously as killers of photoluminescence: Co 2+ [1], Fe 2+ [13,14], and Cr 2+ [15,16]. For all the systems studied so far it has been found that the ground state of the magnetic ion is significantly influenced by the local strain present in a quantum dot.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, optical manipulation of a single magnetic ion spin is possible not only in classical systems with a single Mn 2+ ion in QDs with a relatively low energy gap, CdTe/ZnTe [2][3][4][5][6] and InAs/GaAs [7][8][9], but also in QDs with a higher-energy gap such as CdSe/ZnSe [1,[10][11][12] or in QD systems doped with impurities considered previously as killers of photoluminescence: Co 2+ [1], Fe 2+ [13,14], and Cr 2+ [15,16]. For all the systems studied so far it has been found that the ground state of the magnetic ion is significantly influenced by the local strain present in a quantum dot.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a first‐principle study of the Cr 2+ ‐doped ZnSe has been published . Experimental studies revealed a ferromagnetic p ‐ d exchange in the valence band (in contrast to Mn, Co, and Fe centers, which exhibit antiferromagnetic exchange), and a large spin to strain coupling . The latter makes Cr very promising as a spin qubit for the realization of hybrid spin‐mechanical systems, in which the motion of a microscopic mechanical oscillator would be coherently coupled to the spin state of a single atom .…”
Section: Introductionmentioning
confidence: 99%
“…Typically ultrasound experiments deal with temperature dependences of the phase velocity or attenuation. But in view of possible application in quantum computing, magneto‐acoustic investigation is deemed to be important. We have performed such experiments in wurtzite CdSe:Cr 2+ , fluorite SrF 2 :Cr 2+ , and sphalerite ZnSe:Cr 2+ single crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, the II-VI QD systems were brought to spotlight as a host for single transition metal dopants [7,8]. For example, a single Mn 2+ ion or Cr atom spin in a single CdTe/ZnTe QD was shown to undergo coherent evolution [9,10], which is important from the point of view of quantum information processing. Progress in the solotronics urged us to explore the issue of photon indistiguishability in the II-VI system.…”
Section: Introductionmentioning
confidence: 99%